Latina/o sexualities : probing powers, passions, practices, and policies - Asencio, Marysol, 1960- (Rutgers University Press, 2010)
Situated at the juncture of Latina/o studies and sexualities studies, the contributors to Latina/o Sexualities synthesize and critique the literature and carve a separate space where issues of Latina/o sexualities can be explored given the limitations of prevalent research models. This work compels the current wave in sexuality studies to be more inclusive of ethnic minorities and sets an agenda that policy makers and researchers will find invaluable.